A Comparative Study of the Organellar Genome of Gyrinops versteegii and Aquilaria malaccensis - Hartati, Hartati; Cartealy, Imam Civi; Supatmi, Supatmi; Rahmawati, Syamsidah; Hartati, N Sri; Siregar, Ulfah Juniarti; Siregar, Iskandar Zulkarnaen (Jurnal Manajemen Hutan Tropika, 2024)
Gyrinops versteegii and Aquilaria malaccensis are two important species of the Aquilarieae tribe. The main problem of this tribe is the challenge of species identification that is strongly dependent on the presence of flowers and fruit, which are not always available. The availability of whole genome information is expected to address the problems of species identification. This research aims to construct and compare the chloroplast and mitochondrial genomes of G. versteegii and A. malaccensis from short-read data using the NOVOplasty and GetOrganelle assembler. The chloroplast genome assembly revealed a full-length quadripartite circular structure with sizes of 174.814 bp (G. versteegii) and 174.821–174.822 bp (A. malaccensis), with highly conserved gene and organization. Meanwhile, the mitochondrial genome is multipartite with a size of 400.012 bp (G. versteegii) and 400.000 bp (A. malaccensis), with highly variable genes and organization due to the presence of gene cluster repeats. The LSC/IR/SCC region borders and phylogenetic analysis in chloroplasts indicate variations between the genomes of these two species. The investigation of nucleotide diversity in the chloroplast genome revealed that the trnL-rpl32 region had the highest nucleotide diversity (Pi = 0.03). This information will be useful in the future for a variety of downstream analyses.